The Effectiveness of Using Songs to Improve Students’ Mastery of Present Perfect Tense at The Eighth Grade Students of SMP Negeri 10 Purworejo in The Academic Year of 2014/2015 - Laila Laila Lutfiana (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2019)
The objectives of the study is to find out whether English songs are effective or not to improve students’ understanding of present perfect tense at the eighth grade of SMP N 10 Purworejo in the academic year of 2014/2015. This research was carried out at SMP N 10 Purworejo in five meetings on May 2015. The population of the study is the eighth grade students of SMP N 10 Purworejo. As the sample, the researcher used 64 students of the total population. The researcher used purposive sampling technique to make sample. To collect the data, the researcher used test as the instrument. There were pre-test and post-test. To analyze the data, the researcher used t-test formula. The result of data computation indicates that t-value is 4.65. It means that t-value of this study is higher than the t-table. The t-table is 1.999. It means that using English songs to improve students’ mastery of present perfect tense at the eighth grade of SMP N 10 Purworejo in the academic year of 2014/2015 is effective, therefore Ha is accepted.